PENGARUH PARTISIPASI ANGGOTA DAN LINGKUNGAN KERJA TERHADAP KEBERHASILAN KOPERASI SIMPAN PINJAM 17 AGUSTUS DURI - AraIto, SiskaTio AraIto Tio; ', Caska; ', Makhdalen (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The purpose of theresearch was to knowwhether there is any influence of members participation and working environment on success of Koperasi Simpan Pinjam 17 Agustus Duri. Thisresearch was done on August 2014. The research of this population all members ofKoperasi Simpan Pinjam 17 Agustus Duri as much598members. The samples used were78members. The technique of data analysis was by using SPSS 16.0 version.The conclusion of the test F (Ftest) of the influence of members participation and working environment on success of Koperasi Simpan Pinjam 17 Agustus Duri was found 5,349. F table was found 3,12, so the researcher found that Fhitung > Ftable. It means that there is a influence of members participation and working environment on success of Koperasi Simpan Pinjam 17 Agustus Duri. R2 scale was found 0,125 which is mean the variable of members participation and working environment 12,5% as known as variability from the success of Koperasi Simpan Pinjam 17 Agustus Duri and the rest is influence by the others variables that werw not belong for this research. This similiarit of the double regression was found Y= 14,980+0,171X1+0,244X2 Keywords :membersparticipation, cooperativework environmentandsuccess